PERAN PEREMPUAN DALAM PERKEMBANGAN PENDIDIKAN ISLAM DI ACEH (Kajian Terhadap Kontribusi Wanita dalam Tinjauan Sejarah) - A. Samad, Sri Astuti (LPPM IAIN Parepare, 2016)
Acehnese women contribute significantly in the field of development of Islamic education. Among the well-known figures are Datu Beru and Tengku Fakinah. Datu Beru known as Judge women in the kingdom of Linge in Central Aceh. Although she did not have schools but she could become inspiration in the field of science, especially jurisprudence. Meanwhile, Tengku Fakinah was an educator, a woman scholar in Dayah Lam Diran which was a famous Islamic educational institution in that time. Students who studied at the Islamic boarding school come from various parts of Aceh. They are fully involved in the process of social transformation and intellectual transmission. It is proved that the public role of women in Aceh since in the past did not have social and cultural constraints. In addition, the woman clearly has a major contribution in the field of Islamic education.